Exploring the factors affecting the early identification of developmental delays in children aged 0-5 years by registered healthcare nurses in Bojanala district - Abrahams, Andrea (My University, 2019)
Introduction One of the building blocks for early identification of disabilities in children aged 0-5 years is implementing appropriate measures that are able to identify developmental delays. Seemingly, the RtHB that is being used in South Africa is either not being used in a correct way or the book as a standalone is not sufficient enough to detect developmental delays. Aim To explore Registered Healthcare Nurses perceived factors currently affecting the early identification of developmental delays in children aged 0-5 years in selected facilities in Bojanala District. Method This study applied a qualitative research design using in-depth and semi-structured interviews. Three Key Informants and nine Registered Nurses participated in the study. A thematic analysis was conducted on the data collected. Results Twelve themes were derived as answers for three of the four study objectives. Measures used to detect developmental delays include surveillance, screening, reported information, and knowledge of developmental delays. Health system factors affecting early identification include infrastructural and organizational issues, re-engineering of PHC, Integration of services at PHC facilities, protocols to guide PHC nurses, and fragmentation of services among the different levels of health care facilities. Factors currently contributing to detection of developmental delays were based on service delivery issues, attitude of parents and inaccessibility. Thus, the factors affecting early identification of developmental delays are; the use of informal measures without diagnostic instruments to identify developmental delays, lack of sufficient support from the health system, and limited collaboration between different governmental sectors in detection of childhood disabilities. Conclusion The evidences from the study findings are strong enough to conclude that there are many factors impacting negatively to the detection of developmental delays in children in Bojanala district. There is need for support from the national health sector and collaboration among governmental and non-governmental sectors.
A Research Report submitted in partial fulfilment of the requirement for the degree of Master in Public Health September 2019